Phazeology in Ukrainian’ cognitive processes within ethnic and cultural aspects (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2013)
This article investigates Ukrainian paralinguistical  phraseologism which reveal specific signs in cognitive processes among native speakers and prove their ethnic and cultural determination. Due to idiom comparison in Eastern Slavic languages the character of cognitively determined meaning realization is defined.
Keywords: paralinguistical phraseologism; myremic phraseologism; phonation phraseologism; cognitive processes; ethnic culture; cultural code